Practical use of the Griffiths Scale in older children - Cobos, Francisco; Rodriguez, Cecilia; de Venegas, Ana Victoria (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Comparative scores from the Griffiths Extension Scale for S's from five to eight years of age from two groups are presented. The experimental group was made up of children with cerebral palsy and the control was a group of normal Ss matched by age, sex, and socioeconomic level. The scores were as expected in relation to normalization values for local populations, previously found by the Harvard-ICBF-Comell Research Project on Malnutrition and Mental Development in Bogota, thus suggesting that the administration of this instrument can be, in practice, carried out for normal and abnormal Ss of school age under local conditions in Bogota, Colombia.